Effects of fracturing fluid composition and other factors on improving the oil imbibition recovery of shale reservoir - Shilin Li; Zhongbin Ye; Junqi Wang; Lei Tang; Nanjun Lai (Capillarity, 2023)
Imbibition is an important mechanism of shale reservoir development. In exploring the factors affecting the enhanced recovery of shale reservoirs by imbibition, laboratory spontaneous and forced imbibition experiments were conducted using outcrop cores of shale reservoirs. The effects of imbibition agent composition, fracture, and pressure on imbibition are obtained in this work based on imbibition recovery test findings and imbibition theory. Results show that the imbibition curve includes three stages, namely, imbibition, transition, and stability. Among the components of compound fracking fluid, surfactants have the greatest impact, whereas emulsifiers have the least impact. Complex crack structures and high-temperature environments can improve imbibition recovery. Pressure is inversely proportional to imbibition recovery in the highly stress-sensitive shale reservoir. In addition, the throughput time of the imbibition agent has an optimal value in the shale reservoir. After the huff-n-puff time exceeds the optimal value, the imbibition agent should be replaced to continuously improve the imbibition effect. The research results can serve as a basis for enhancing oil recovery through imbibition. Document Type: Original article Cited as: Li, S., Ye, Z., Wang, J., Tang, L., Lai, N. Effects of fracturing fluid composition and other factors on improving the oil imbibition recovery of shale reservoir. Capillarity, 2023, 9(3): 45-54. https://doi.org/10.46690/capi.2023.12.01